GAP management status and regional indicators of threats to biodiversity - Stoms, D. M. (Landscape Ecology, 2000)
Conservation assessment requires quantitative criteria for evaluating the relative degree of threat faced by species or ecological communities. Identifying appropriate criteria for communities is complicated because the species inhabiting them can have many different responses to land uses and other forms of environmental stress. The Gap Analysis Program (GAP) uses summary data on the proportion of the community that is protected as an estimate of its vulnerability. Management status from a gap analysis of California was compared with three ecological indicators (permitted land uses, human population growth, and the spatial extent of road effects) that more directly represent impacts on biodiversity. The classification of management status appears to provide a crude first approximation of these three indicators. Public and private lands that are not formally protected were susceptible to extensive land use conversion or resource extraction in both rural and urban settings. Some plant community types are more susceptible to future infringement by human population increases that were not well predicted by management status alone. Other community types are heavily roaded despite being moderately well protected. It is suggested that indicators such as future growth and current road effects could complement status in rating the potential vulnerability of plant communities and setting conservation priorities. The choice of indicators will depend on the threatening processes in a given region and the availability of spatial data to map or model them.
Keywords: roadedness biodiversity ecological indicators California gap analysis land use projected human population growth road density index zoning